2010
DOI: 10.1097/aln.0b013e3181c38c25
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Reversal, and Prevention of Opioid-induced Respiratory Depression

Abstract: Opioid treatment of pain is generally safe with 0.5% or less events from respiratory depression. However, fatalities are regularly reported. The only treatment currently available to reverse opioid respiratory depression is by naloxone infusion. The efficacy of naloxone depends on its own pharmacological characteristics and on those (including receptor kinetics) of the opioid that needs reversal. Short elimination of naloxone and biophase equilibration half-lives and rapid receptor kinetics complicates reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
439
1
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(462 citation statements)
references
References 107 publications
(123 reference statements)
8
439
1
14
Order By: Relevance
“…This issue has received considerable attention, [26][27][28][29] and an appreciable number of preventable catastrophic accidents continue to occur. However, while increased monitoring of at-risk patients (particularly when patient-controlled analgesia is used) seems indicated, consensus has not been achieved regarding a ''get to zero'' approach of eliminating these mishaps.…”
Section: Monitoring Issuesmentioning
confidence: 99%
“…This issue has received considerable attention, [26][27][28][29] and an appreciable number of preventable catastrophic accidents continue to occur. However, while increased monitoring of at-risk patients (particularly when patient-controlled analgesia is used) seems indicated, consensus has not been achieved regarding a ''get to zero'' approach of eliminating these mishaps.…”
Section: Monitoring Issuesmentioning
confidence: 99%
“…Studies indicated that opioid drugs can lead to respiratory depression and acidaemia [7]. Aguiler et al, [2000] postulated that acidaemia decreases the binding of calcium to plasma protein with subsequent increases in the ionized calcium [23].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst respiratory depression can be effectively treated by the opioid antagonists naloxone and naltrexone, analgesic efficacy is also reduced. Agents such as the a-amino-3-hydroxy-5-methyl-4-isoxazole-proprionic acid (AMPA) receptor agonists (ampakines) and minocycline have been shown to suppress opioid-induced respiratory depression without affecting analgesic efficacy 81,82 . Serotonin (5-hydroxy tryptamine,5-HT) agonists, by virtue of the role of 5-HT neurones in the maintenance of respiratory drive, have also been evaluated for the suppression of opioid-induced respiratory depression, but not found to be effective 82 .…”
Section: Novel Molecular Developmentsmentioning
confidence: 99%
“…Agents such as the a-amino-3-hydroxy-5-methyl-4-isoxazole-proprionic acid (AMPA) receptor agonists (ampakines) and minocycline have been shown to suppress opioid-induced respiratory depression without affecting analgesic efficacy 81,82 . Serotonin (5-hydroxy tryptamine,5-HT) agonists, by virtue of the role of 5-HT neurones in the maintenance of respiratory drive, have also been evaluated for the suppression of opioid-induced respiratory depression, but not found to be effective 82 . In contrast to the approaches designed to mitigate the adverse effects of classical opioids outlined above, novel non-classical molecules with similar efficacy but reduced side effects are in clinical development.…”
Section: Novel Molecular Developmentsmentioning
confidence: 99%